Ginkgolic Acid Inhibits Coronavirus Strain 229E Infection of Human Epithelial Lung Cells - Maimoona S. Bhutta; Daniel G. Sausen; Elisa S. Gallo; Harel Dahari; Gustavo F. Doncel; Ronen Borenstein (MDPI AG, 2021)
Since December 2019, the COVID-19 pandemic has affected more than 200 million individuals around the globe and caused millions of deaths. Although there are now multiple vaccines for SARS-CoV-2, their efficacy may be limited by current and future viral mutations. Therefore, effective antiviral compounds are an essential component to win the battle against the family of coronaviruses. Ginkgolic Acid (GA) is a pan-antiviral molecule with proven effective in vitro and in vivo activity. We previously demonstrated that GA inhibits Herpes Simplex Virus 1 (HSV-1) by disrupting viral structure, blocking fusion, and inhibiting viral protein synthesis. Additionally, we reported that GA displays broad-spectrum fusion inhibition encompassing all three classes of fusion proteins, including those of HIV, Ebola, influenza A, and Epstein Barr virus. Here, we report that GA exhibited potent antiviral activity against Human Coronavirus strain 229E (HCoV-229E) infection of human epithelial lung cells (MRC-5). GA significantly reduced progeny virus production, expression of viral proteins, and cytopathic effects (CPE). Furthermore, GA significantly inhibited HCoV-229E even when added post-infection. In light of our findings and the similarities of this family of viruses, GA holds promising potential as an effective antiviral treatment for SARS-CoV-2.